2014
DOI: 10.3390/ijms150915512
|View full text |Cite
|
Sign up to set email alerts
|

Resveratrol Induces the Expression of Interleukin-10 and Brain-Derived Neurotrophic Factor in BV2 Microglia under Hypoxia

Abstract: Microglia are the resident macrophages of the central nervous system (CNS) and play an important role in neuronal recovery by scavenging damaged neurons. However, overactivation of microglia leads to neuronal death that is associated with CNS disorders. Therefore, regulation of microglial activation has been suggested to be an important target for treatment of CNS diseases. In the present study, we investigated the beneficial effect of resveratrol, a natural phenol with antioxidant effects, in the microglial c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
29
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(33 citation statements)
references
References 81 publications
4
29
0
Order By: Relevance
“…Other authors also found that hypoxia reduced basal and induced IL-10 protein and gene expressions 32 . Taken together, these data suggest that hypoxia significantly impairs IL-10 expression in macrophages, and this impairment is not ameliorated by MSCs.…”
Section: Discussionmentioning
confidence: 92%
“…Other authors also found that hypoxia reduced basal and induced IL-10 protein and gene expressions 32 . Taken together, these data suggest that hypoxia significantly impairs IL-10 expression in macrophages, and this impairment is not ameliorated by MSCs.…”
Section: Discussionmentioning
confidence: 92%
“…Glatiramer acetate, an immunomodulatory agent used in relapsing-remitting multiple sclerosis, was shown to induce secretion of IL-10 by microglial cells [95]. Resveratrol administration to a microglial cell line prevented hypoxia-induced injury by up-regulating IL-10 and controlling inflammation [96]. Collectively, these reports show that the molecules present in the microenvironment can impact IL-10 production by microglia, thus shaping the outcome of the inflammatory response.…”
Section: Cellular Sources Of Il-10 In the Cnsmentioning
confidence: 99%
“…Many studies showed that resveratrol treatment decreases inflammatory burden by reducing microglial activation in in vivo (Girbovan and Plamondon, 2015; Shin et al, 2010; Simao et al, 2012a) and in vitro (Song et al, 2014) models of ischemic stroke. Resveratrol has also been shown to reduce edema (Ren et al, 2011; Yousuf et al, 2009) and prevent the release of pro-inflammatory cytokines (Shin et al, 2010; Song et al, 2014). Furthermore, resveratrol alleviates inflammation by decreasing ROS levels which are known to activate immune cells (Khodr and Khalil, 2001).…”
Section: Anti-inflammatory Properties Of Resveratrolmentioning
confidence: 99%